Cultural Transformation and Social Identity in the Digital Age - Judijanto, Loso; Merung , Arteurt Yoseph; Rosalia, Olyvia; Firayani, Firayani; Noviya, Anis (PT. Anagata Sembagi Education, 2025)
The transformation of culture and social identity in the digital age is becoming an increasingly complex phenomenon along with the development of information and Communication Technology. This study aims to understand how digital media affects the construction of social identity and cultural change in society. Using a qualitative approach, this study adopts the methods of digital ethnography, discourse analysis, and case studies to explore the experiences of individuals and communities in the digital space. The results showed that social identity becomes more flexible and can be reconstructed through interactions on social media. In addition, the phenomenon of glocalization occurs, in which the local culture adapts to the global culture in digital format. However, challenges such as cultural homogenization, filter bubbles and digital Identity Security also arise in this process. In conclusion, digital media not only accelerates cultural transformation but also creates new dynamics in the formation of social identity. Further studies are needed to explore the long-term impact of this phenomenon.